2019
DOI: 10.1016/j.omtn.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A Small RNA Transforms the Multidrug Resistance of Pseudomonas aeruginosa to Drug Susceptibility

Abstract: Bacteria with multiple drug resistance (MDR) have become a global issue worldwide, and hundreds of thousands of people’s lives are threatened every year. The emergence of novel MDR strains and insufficient development of new antimicrobial agents are the major reasons that limit the choice of antibiotics for the treatment of bacterial infection. Thus, preserving the clinical value of current antibiotics could be one of the effective approaches to resolve this problem. Here we identified numerous novel small RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…sRNAs affect the stabilities and translation efficiencies of mRNAs through complementary base pairing, which is a key regulatory mechanism of bacterial gene expression (31,38,39). Although bacterial sRNAs affect a wide range of biological processes, including energy utilization and metabolism, pathogenicity, and antibiotic resistance, our understanding of the regulation of sRNAs is still limited (40)(41)(42)(43). Ribonucleases play an important role in cellular RNA metabolism processes, such as mRNA degradation and rRNA/tRNA maturation, and have emerged as the main posttranscriptional regulators of sRNAs (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…sRNAs affect the stabilities and translation efficiencies of mRNAs through complementary base pairing, which is a key regulatory mechanism of bacterial gene expression (31,38,39). Although bacterial sRNAs affect a wide range of biological processes, including energy utilization and metabolism, pathogenicity, and antibiotic resistance, our understanding of the regulation of sRNAs is still limited (40)(41)(42)(43). Ribonucleases play an important role in cellular RNA metabolism processes, such as mRNA degradation and rRNA/tRNA maturation, and have emerged as the main posttranscriptional regulators of sRNAs (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies point toward that direction, and have been excellently reviewed by Lalaouna et al (2014), Dersch et al (2017), Felden and Cattoira (2018). The antibiotic susceptibility of multidrug-resistant (MDR) Pseudomonas aeruginosa was dramatically altered when AS1974 sRNA was overexpressed (Law et al, 2019). Authors of the study carried out a first screening on the sRNAs repertoire on three MDR clinical isolates, having found three small-regulatory RNAs that were significantly downregulated.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Converting MDR bacteria to drug hyper susceptible cells is a potential approach to fight against MDR infection. It has been recently shown that the overexpression of the sRNA AS1974 in clinical isolates of MDR P. aeruginosa induces drug hyper susceptibility [ 257 ].…”
Section: Antimicrobial Strategies Related With Tcs and Associated mentioning
confidence: 99%